Bodily Violence, Agency, and Animals. Issue 2 (16th January 2018) - Lin, Zi
Abstract: Ethical theories in the Kantian tradition tend to centre heavily on rational agency, so it may appear challenging for such theories to account for the wrongness of bodily violence, especially the wrongness of bodily violence to animals who lack rationality. This article develops a Kantian explanation for the pro tanto wrongness of killing or injuring animals who have agency and lack rationality, based on a Kantian explanation for the pro tanto wrongness of killing or injuring people. Even though morality is grounded in the will of rational agents or the value of rational agency, one does not have to be a rational agent to be morally considerable.